2015
DOI: 10.1152/japplphysiol.00533.2014
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction in children and adolescents conceived by assisted reproductive technologies

Abstract: Assisted reproductive technologies (ART) predispose the offspring to vascular dysfunction, arterial hypertension, and hypoxic pulmonary hypertension. Recently, cardiac remodeling and dysfunction during fetal and early postnatal life have been reported in offspring of ART, but it is not known whether these cardiac alterations persist later in life and whether confounding factors contribute to this problem. We, therefore, assessed cardiac function and pulmonary artery pressure by echocardiography in 54 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
4
37
1
Order By: Relevance
“…Based on emerging data showing that the early embryo is particularly sensitive to environmental insults, we speculated that ART alters cardiovascular function in the offspring. In line with this speculation, we found that young, apparently healthy ART children display signs of premature vascular ageing of the systemic circulation together with pulmonary vascular dysfunction predisposing to exaggerated hypoxic pulmonary hypertension [17][18][19][20]. Most importantly, recent data indicate that ART-induced vascular dysfunction translates into increased arterial blood pressure.…”
Section: Role Of Epigenetics In Hypertensionsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on emerging data showing that the early embryo is particularly sensitive to environmental insults, we speculated that ART alters cardiovascular function in the offspring. In line with this speculation, we found that young, apparently healthy ART children display signs of premature vascular ageing of the systemic circulation together with pulmonary vascular dysfunction predisposing to exaggerated hypoxic pulmonary hypertension [17][18][19][20]. Most importantly, recent data indicate that ART-induced vascular dysfunction translates into increased arterial blood pressure.…”
Section: Role Of Epigenetics In Hypertensionsupporting
confidence: 78%
“…These differences in blood pressure between ART and control children are clinically important, as childhood blood pressure tracks into later life [23]. Parenthetically, it is well known that arterial hypertension is often associated with insulin resistance [24], and defective nitric oxide-dependent insulin stimulation of blood flow and substrate delivery to skeletal muscle tissue, which leads to insulin resistance in experimental animal models and humans, may represent an underlying mechanism [20,25,26]. Accordingly, a recent study demonstrated insulin resistance in young adults conceived by ART [27], suggesting that ART-induced vascular dysfunction may facilitate diabetes later in life.…”
Section: Role Of Epigenetics In Hypertensionmentioning
confidence: 99%
“…Gratacos et al showed that ART is associated with in utero cardiac remodelling that persists in 6 month old infants [55]. We subsequently demonstrated that cardiac alterations persist into adolescence, as evidenced by larger right ventricular end-diastolic volume and diastolic dysfunction at high altitude [56].…”
Section: Early Embryonic Insults: Assisted Reproductive Technology (Asupporting
confidence: 52%
“…Scherrer and colleagues also found that high altitude conditions induced a 30% increase in systolic pulmonary artery pressure in IVF/ICSI children by comparison with naturally conceived children [40]. In a separate report, the same research group observed increased right ventricle end-diastolic area and diastolic dysfunction in IVF/ICSI children at high altitude, but not at low altitude [42]. In both cases, pulmonary hypertension differences were observed only under hypoxic stress.…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 99%